Effect of Vertebral Fracture on Auxological Profiles of Children Undergoing Acute Lymphoblastic Leukemia Treatment - Ahn, Moon Bae; Kim, Seongkoo; Cho, Won Kyoung; Lee, Jae Wook; Jung, Min Ho; Chung, Nack-Gyun; Cho, Bin; Suh, Byung-Kyu (Frontiers in Pediatrics, 2021)
Background: Acute lymphoblastic leukemia (ALL) is the most common pediatric malignancy, and children with ALL often experience skeletal morbidity such as vertebral fractures (VF) during and after ALL treatment. Among various treatment-associated factors that affect growth pattern, the presence of VF might trigger growth impairment. Objective: This study aimed to investigate the overall VF incidence following childhood ALL treatment and examined the association of VF with growth. Methods: Children diagnosed with ALL whose treatment was completed between 2 and 15 years of age and who were screened with lateral thoracolumbar spine radiographs were enrolled. Clinical data, including anthropometric parameters were obtained at leukemia diagnosis (LD), treatment completion (TC), and 12 months following TC while VF assessment were obtained at TC and 12 months following TC. Results: In total, 155 children were included, and height status was decreased, whereas weight and BMI status were increased throughout three observational points. VF incidence at TC was 18.7%. Height status were lower in children with VF at LD, TC, and 12 months following TC, while a greater height decline was observed during the treatment period. Age and height status at LD and average glucocorticoid (GC) dose were associated VF incidence at TC. The presence of VF was a significant risk factor of height decline during the treatment period. Conclusion: A substantial number of children experienced VF following ALL treatment completion, and the presence of VF might adversely affect auxological status in children. VF detection by routine surveillance throughout childhood ALL treatment is recommended to try to prevent compromised growth.